Conventional and advanced exergetic analysis for the combined cycle of power plant with gas turbine of a refinery (2021)
This article shows the results of the performance study of a combined cycle plant made up of a Siemens STG-800 gas turbine and a MACCHI heat recovery boiler (HRSG) designed to produce 47.5 MW of electricity and 81908 kg / h of steam operating under ISO conditions (15 ° C and 60% relative humidity and 1 atm), the system is part of the steam and electric power generation section of a crude oil refinery in the city of Cartagena de Indias. The objective of this research is to quantify the real inefficiencies in each of the equipment applying conventional and advanced exergetic analysis, to achieve this the investigation has been ordered as follows: first, the basic thermodynamics at the equipment boundaries is defined, define performance parameters that compare the adjustment of the thermodynamic model with the values provided by the manufacturer, the rate of exergy destruction and exergy efficiency are obtained from conventional analysis, advanced exergetic analysis allows obtaining avoidable, unavoidable, endogenous, exogenous exergies and the combined, finally, the mexogenous exergetic analysis allows to know the amount of energy that is lost due to the interactions between the equipment. The thermodynamic model is adjusted with an average error of 2% using design KPIs such as net power, heat rate and thermal efficiency, it was obtained that the exergy destruction reaches 83.5MW, 15% is avoidable and the 8% is avoidable endogenous, the mexogenous analysis shows that inefficiencies in the compressor refer to all equipment, by focusing efforts on improving its conditions, up to 25% of the total exergy destruction can be recovered.